Social vulnerability of unaccompanied migrant children: a view from the urban area of Altar, Sonora, Mexico - Cabrera Duarte, Mario Alexander; Valdéz Gardea, Gloria Ciria (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article is the result of research carried out by the authors on the social vulnerability of unaccompanied migrant children in the urban area of Altar, Sonora, during the years 2010-2011. The main techniques used for data collection were participant observation and semi-structured interview. The results offered are limited to evidence the social vulnerability suffered by unaccompanied migrant children, by making use of the services of food, accommodation and health. Which exposes them to a number of risks, such as food shortages, the loss of their few belongings, the drug, the physical, the suffering of diseases and limited access to medical care aggressions.